Monetary Policy and Sectoral Shocks : Did the Federal Reserve React Properly to the High-Tech Crisis? - Raddatz, Claudio; Rigobon, Roberto (World Bank, Washington, DC, 2014)
The authors present an identification strategy that allows them to study the sectoral effects of monetary policy and the role that monetary policy plays in the transmission of sectoral shocks. They apply their methodology to the case of the United States and find some significant differences in the sectoral responses to monetary policy. They also find that monetary policy is a significant source of sectoral transfers. In particular, a shock to equipment and software investment, which one identifies with the high-tech crisis, induces a response by the monetary authority that generates a temporary boom in residential investment and durables consumption but has almost no effect on the high-tech sector. Finally, the authors perform an exercise evaluating the model's predictions about the automatic and more aggressive monetary policy response to a shock similar to the one that hit the United States in early 2001. They find that the actual drop in interest rates is in line with the predictions of the model.